"PRESUMED SYSTEMIC BACILLE CALMETTE-GUÉRIN DISEASE AFTER BCG VACCINATION: REPORT OF A CLINICAL CASE " - P. Tabatabaie; M. Abedini; E. Fayazzadeh1 M. Monajemzadeh (Acta Medica Iranica, 2006)
BCG (bacille Calmette–Guérin) vaccine is administered worldwide to prevent severe forms of tuberculosis. It is considered to be safe; however, occasional complications are seen. The most serious complication is BCGosis. We report a case of BCGosis with granulomatous hepatitis and acid-fast bacilli in liver and spleen. We treated the patient with antituberculosis drugs without any response to treatment.